2006
DOI: 10.1189/jlb.0406236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on IL-18-initiated immune response in human monocytes

Abstract: Nicotine is thought to inhibit the production of proinflammatory cytokines from macrophages through an anti-inflammatory pathway that is dependent on nicotinic acetylcholine receptor alpha7 subunit (alpha7-nAChR). IL-18, an important proinflammatory cytokine, is reported to induce the expression of adhesion molecules on monocytes, thus enhancing cell-to-cell interactions with T-cells and contributing to IL-18-initiated cytokine production. Accordingly, inhibition of IL-18 suppresses systemic inflammatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 24 publications
2
29
0
1
Order By: Relevance
“…These results imply that the additional increase in PGE 2 by the combination of nicotine and AGEs might, at least partially account for the suppressive effect of nicotine on AGE-2-and AGE-3-induced enhancement of adhesion molecule expressions and cytokine production. We observed a similar pattern of inhibitory effects of nicotine on lipopolysaccharide (LPS)-and interleukin (IL)-18-induced activation of monocytes in human PBMCs via ␣7-nAChR Takahashi et al, 2006). Nicotine induced PGE 2 production in monocytes treated with LPS and IL-18 via ␣7-nAChR.…”
Section: Discussionsupporting
confidence: 55%
“…These results imply that the additional increase in PGE 2 by the combination of nicotine and AGEs might, at least partially account for the suppressive effect of nicotine on AGE-2-and AGE-3-induced enhancement of adhesion molecule expressions and cytokine production. We observed a similar pattern of inhibitory effects of nicotine on lipopolysaccharide (LPS)-and interleukin (IL)-18-induced activation of monocytes in human PBMCs via ␣7-nAChR Takahashi et al, 2006). Nicotine induced PGE 2 production in monocytes treated with LPS and IL-18 via ␣7-nAChR.…”
Section: Discussionsupporting
confidence: 55%
“…Besides Aβ neurotoxicity, another feature of AD is the loss of cholinergic projections and decline of nAChRs from the early stage of AD (Oddo and LaFerla, 2006). In this regard, recent studies have reported the existence of a cholinergic control of microglial activation by showing that nicotine reduced LPSinduced production of TNF-α and IL-18, indicating that nicotine has immunosuppressive effects (Shytle et al, 2004;De Simone et al, 2005;Suzuki et al, 2006;Takahashi et al, 2006). On the other hand, nicotine treatment significantly increased the expression of COX-2 and the synthesis of PGE2 in LPS-stimulated microglia, and even enhanced TNF-α production in BzATP-stimulated microglia, suggesting a neuroprotective effect of nicotine at low concentration (De Simone et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since several articles recently described an immuno-regulatory role of nicotine, [25][26][27] we tested if nicotine might influence OPN-production by alveolar macrophages. Therefore, we stimulated BAL-cells from healthy, currently smoking and nonsmoking individuals with nicotine.…”
Section: Discussionmentioning
confidence: 99%